IMPLEMENTASI KURIKULUM MERDEKA PADA ANAK BERKEBUTUHAN KHUSUS - ADEL AURENT MANSUR; ABDUL LATIF FATKHURIZA; DWIKI HARI WIJAYA (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2022)
Starting from many problems regarding to curriculum without exception the curriculum for children with special needs. This study aims to find out how implementation of the curriculum for children with special needs in Unesa Labschool and what are the supporting and inhibiting factors in carrying out the implementation of the curriculum. This research is a field research using a quantitative descriptive analytic approach. The results of this study are: the implementation of the curriculum at SMK Labschool UNESA Surabaya starts from the curriculum planning contained in the RPPM, and RPPH which refers to the independent learning curriculum which is then modified by reducing learning achievement standards according to the needs and abilities of students. Adaptation of the child’s curriculum is based on the pattern of adaptation and the ability of the child’s education. RPPH is designed to be as flexible as possible because classes are heterogeneous. The core learning activities refer to the development of Religious and Moral Values, Physical Motor, Cognitive, Language, Social Emotions, Art and Creativity. The learning media used puts forward the principles of effectiveness and efficiency and safety for students. The scoring system is based on the assessment by the teacher and the results of therapy.